Evaluación del ruido ambiental generado por aeronaves del aeropuerto Carlos Martínez de Pinillos en la localidad de Huanchaco, región La Libertad, año 2019 - Aredo Chinga, Betty Elizabeth (2019)
The present research work was performed in the district of Huanchaco in the urban areas: P.I. Las Lomas, AA.HH. Las Lomas II and hamlet Bello Horizonte, with the purpose of evaluating and analyzing the noise generated by the aeronautical activities (landing, take-off and overflight) of the Carlos Martínez de Pinillos Airport. The areas of study were determined by a prior recognition of aircrafts flight paths and its possible affectation in them. Subsequently, essential information about zones, flight times, etc. was collected. Then, a survey designed under the model proposed in D.S. 262-2016-MINAM. Lineamientos para la elaboración de Planes de acción para la Prevención y Control de la Contaminación Sonora, was applied, to a sample of 430 people in total, during a period of 1 month. With a prior knowledge of the D.S. D.S. 085-2003 PCM Estándares de Calidad Ambiental para Ruido and Protocolo Nacional de Monitoreo de Ruido Ambiental, the monitoring was planned in 28 stations and the measurements were taken on different days of the week from Monday to Sunday, both in the daytime as a night during a period of 1 month. The information obtained was processed to determine the Equivalent Continuous Sound Pressure Level- Weighting A (LAeqT) and the Noise Map was elaborated. In this sense, the results obtained were compared with ECAs for the residential area and it was observed that more than 50% of the results exceeded 60 dB for Daytime and 50 dB for Night established in the regulations, being P.I Las Lomas and AA.H H. Las Lomas II the most affected areas, due to poor territorial planning, environmental education, and lack of stricter environmental policies of the interested parties